HUBUNGAN TINGKAT PENDIDIKAN DENGAN PENGETAHUAN IBU TENTANG TUMBUH KEMBANG ANAK BALITA DI SRAGEN - Retno Ambarwati; Nita Yunianti Ratnasari; Kristiana Puji Purwandari (Akademi Keperawatan Giri Satria Husada Wonogiri, 2019)
An important period in child development is the toddler period. In this toddler the development of language skills, creativity, social awareness, emotional and intelligence goes very fast and is the cornerstone of subsequent developments. Problems of growth and development of children under the age of five (Toddler) in life are things that `must be known and studied by a mother. Monitoring the growth and development of infants is one of the important activities to find out the obstacles in growth (growth faltering) early. Mother's education is one of the important factors in child development. Mother's education is good, so she can receive all information from outside, especially about how to take good care of children and maintain good children's health.The Objective of this research is to analyze the relationship between mother's education level and the level of mother's knowledge about the growth and development of children under five in Anna Sragen Kindergarten. This research is observational with cross sectional approach. The research subjects were 20 respondents. Sampling with a simple random sampling system. Data on maternal education was obtained from the results of questionnaires and knowledge of mothers through questionnaires. Data analysis using Chi-Square test. The results of the test of the relationship between the level of education with the level of knowledge of mothers about the growth and development of children under five shows the value of p = 0.013 (p <0.05). The OR value from the above results shows that mothers with low education levels are more at risk of having less knowledge about child development and development of toddlers by 16.3 times compared to mothers who have high education levels (OR = 16,349). There is a significant relationship between the level of mother's education with the level of mother's knowledge about the growth and development of children under five. Periode penting dalam tumbuh kembang anak adalah masa balita. Pada masa balita ini perkembangan kemampuan berbahasa, kreativitas, kesadaran sosial, emosional dan intelegensia berjalan sangat cepat dan merupakan landasan perkembangan berikutnya. Masalah pertumbuhan dan perkembangan anak usia dibawah lima tahun ( Balita) didalam kehidupan merupakan hal yang `harus diketahui dan dipelajari oleh seorang ibu. Pemantauan pertumbuhan dan perkembangan balita adalah salah satu kegiatan penting untuk mengetahui adanya hambatan dalam pertumbuhan (growth faltering) secara dini. Pendidikan ibu merupakan salah satu faktor yang penting dalam tumbuh kembang anak. Pendidikan ibu baik, maka dapat menerima segala informasi dari luar terutama tentang cara mengasuh anak yang baik dan menjaga kesehatan anak yang baik. Tujuan penelitian ini untuk menganalisa hubungan tingkat pendidikan ibu dengan tingkat pengetahuan ibu tentang tumbuh kembang anak balita di TK Anna Sragen. Penelitian ini bersifat obvservasional dengan pendekatan cross sectional. Subjek penelitian sebesar 20 responden. Pengambilan sampel dengan sistem simple random sampling. Data pendidikan ibu diperoleh dari hasil pengisian kuesioner dan Pengetahuan ibu melalui pengisian kuesioner. Analisis data menggunakan uji Chi- Square. Hasil uji hubungan antara tingkat pendidikan dengan Tingkat pengetahuan ibu tentang tumbuh kembang anak balita menunjukkan nilai p=0,013 (p<0,05). Nilai OR dari hasil di atas menunjukkan bahwa ibu dengan tingkat pendidikan rendah lebih berisiko memiliki pengetahuan yang kurang tentang tumbuh kembang anak balita sebesar 16,3 kali dibandingkan dengan ibu yang memiliki tingkat pendidikan tinggi (OR=16,349). Terdapat hubungan yang signifikan antara tingkat pendidikan ibu dengan tingkat pengetahuan ibu tentang tumbuh kembang anak balita.